Model for Optimizing the Ratios of the Company Suppliers in Slovak Automotive Industry - Jaroslava Kádárová (MDPI AG, 2021)
The Slovak automotive industry consists of various companies and suppliers, with different positions in the supply chain for automotive manufacturers. The accuracy of component deliveries and their quality affect the ultimate competitiveness of the entire automotive industry. The creation of strategic partnerships and stable supplier–customer relationships is currently a necessity. The aim of the article is to design the model for optimizing the ratio of the company suppliers in the Slovak automotive industry. The basis for designing the model was the results of our own research focused on the quality and timeliness of component deliveries from various suppliers. Supply chain members work with multiple subcontractors, using multiple subcontractors to supply the same components. We analyzed the overall quality of delivered components at a certain stage of the supply chain. The quality of the supplied components was the sum of all items from all suppliers. The aim of the proposed model is to determine the optimal percentage of individual suppliers of a particular part so as to minimize the overall risk associated with the supply and inventory of a particular part for the customer. Research methodology was focused on identification of the key performance indicators and key risk indicators of components deliveries by different suppliers. Those indicators provide a basis for the effective results of further research. We designed and used an algorithm for preparing and evaluating the model for optimizing the ratio of the company suppliers in the Slovak automotive industry. This research used modeling methods, simulations, and optimization models. The proposed model was verified in the specific conditions of the automotive supply chain. Deliveries from two subcontractors were simulated. Based on the results of the simulations, the optimal supply ratio of the two subcontractors was determined for a specific component of a member of the supply chain at a higher level. The results of the research can be useful for different suppliers in the Slovak automotive industry. By partially modifying the model and adapting it for different conditions in other industries, the model of optimizing the distribution of supply from individual suppliers can be used for other supply chains.